Scope determination in software process lines (2019)
Software process is a recognized way for guiding the software development, however having a process does not necessarily mean, that it fits all specific situations. Consequently, the software processes normally require being tailored to each specific context to achieve the rightest adapted process. However, software process tailoring is a challenging research area because it is a knowledge-demanding intensive activity: it requires experience, knowledge and it is time-consuming. In recent years, different approaches have emerged for tailoring the software process. One of the recent strategies for tailoring software processes is to plan and manage their variability through a production strategy following a Software Process Lines Engineering (SPrLE) approach, which focuses on defining a software process line (SPrL) instead of independent processes. In Software Process Line Engineering (SPrLE) a crucial activity is the delimitation of the scope of the SPrLs, where establishing the processes and the characteristics of the processes that reuse, as well as specify the situations in which these processes they will be suitable. The scope definition is a complex and critical activity, which may facilitate or hinder the organizations from achieving a viable SPrL solution. Furthermore, the scope definition approach does not have a clear direction so that the software industry can make its incorporation in an appropriate way. The lack of guiding elements in the extraction, analysis, and modeling of the scope makes these approaches inappropriate for direction this vital activity whose definition impact in the success of the software process lines definition. This thesis presents SpeTion-SPrL (ScoPE determinaTION in Software Process Lines) approach for systematic scope determination in the Software Process Lines. It is based on the identification of the need for projects and products with respect to the process elements. It identifies the needs and their corresponding correlation with the process assets through a suitability level that allows quantitatively select and make adaptation decisions on the process elements. SpeTion-SPrL was built under the principles of systematicity, integrality, properly conducted and materializable, whose support is determined by the different elements that make it up. It integrates elements of three main approaches: SCOPE, CASPER and SPL scoping and it was defined using systematic techniques and refined through its evaluation.